Burnout and Human Needs Fulfillment Based on Watson’s Ninth Carative Factor: A Correlational Study Among Hemodialysis Nurses in Malang, Indonesia - Sassanti, Suci Wulandari; Wihastuti, Titin Andri; Ismail, Dina Dewi Sartika Lestari (Chakra Brahmanda Lentera Institute, 2025)
Background: Burnout among hemodialysis nurses has reached critical levels globally. Grounded in Watson's Theory of Human Caring, this study examined the relationship between Watson's ninth carative factor (assisting with human needs gratification while preserving dignity and wholeness) and burnout levels among hemodialysis nurses. Methods: A cross-sectional correlational study was conducted among 113 hemodialysis nurses from the Indonesian Dialysis Nurses Association in Malang (April-May 2025). Stratified random sampling used Slovin's formula with 5% margin of error. Inclusion criteria: actively working hemodialysis nurses providing informed consent. Exclusion criteria: nurses on leave, retired, experiencing health issues, or in training programs. Burnout (independent variable) was measured using Professional Quality of Life Scale version V (ProQOL-V) burnout subscale (10 items, 5-point Likert, scores 10-55). Human needs fulfillment (dependent variable) used 10 items from Caring Nurse-Patient Interactions Scale (5-point Likert, scores 10-50). Both instruments underwent pilot testing (n=10), demonstrating validity (r>0.632) and reliability (Cronbach's α>0.6). Data collection utilized online surveys. Statistical analysis employed Spearman's correlation (α=0.05). . Results: Participants were predominantly female (59.3%), aged 36-45 years (48.7%), with bachelor's degrees plus nursing credentials (53.1%), and >5 years experience (65.5%). Burnout distribution: 56.6% low, 43.4% moderate, 0% high. Human needs fulfillment: 90.3% high, 9.7% moderate, 0% low. Spearman's analysis revealed significant negative correlation between burnout and human needs fulfillment (ρ=-0.446, p<0.001, moderate effect size). Conclusion: Higher implementation of Watson's ninth carative factor significantly reduces burnout among hemodialysis nurses. The theoretical model demonstrates that addressing patients' holistic needs while preserving dignity creates meaningful work experiences protecting nurses from burnout. Healthcare organizations should integrate Watson's Theory into professional development programs. Future longitudinal studies across diverse contexts are recommended to establish causal relationships.